2012
DOI: 10.1111/j.1747-6593.2011.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Water quality index as a simple indicator of watersheds pollution in southwestern part of Iran

Abstract: The Karun River is the most important watershed in the southwestern region of Iran. Water quality parameters were sampled from October 2006 through July 2007 at three sites along a 4 km gradient, covering both the wet and the dry season. Surface water was collected at three different stations per site (close to the banks and in the middle of the river) and analysed for 14 parameters and heavy metals. The values of 1300, 196.8 and 4042.9 ppm for chemical oxygen demand, biochemical oxygen demand and chloride, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…According toAmin et al (2009), who reported that Cu and Zn may be the most detrimental elements to gastropod populations in the mangrove area of Dumai coastal waters, the high concentrations of Cu and Zn in the investigated area may hurt the studied organisms. cause great threat to all marine organisms, including fish crustacean, phyto-and zoo-plankton, macroalgae and filter feeders(Dadolahi-Sohrab et al, 2011). The obtained results exhibited that the infestation of Patella caerulea by Poly.…”
mentioning
confidence: 86%
“…According toAmin et al (2009), who reported that Cu and Zn may be the most detrimental elements to gastropod populations in the mangrove area of Dumai coastal waters, the high concentrations of Cu and Zn in the investigated area may hurt the studied organisms. cause great threat to all marine organisms, including fish crustacean, phyto-and zoo-plankton, macroalgae and filter feeders(Dadolahi-Sohrab et al, 2011). The obtained results exhibited that the infestation of Patella caerulea by Poly.…”
mentioning
confidence: 86%
“…Studies on Iranian rivers are prevalently focused on a single specific issue, such as hydropower production (e.g., Karamouz et al, 2005;Dariane andMomtahen 2009), flooding (e.g., Heidari, 2009), or water quality (e.g., Dadolahi-Sohrab et al, 2012). However, these works lead to solutions that may appear effective with respect to a single point of view, but are actually unsatisfactory when evaluated from a larger, multiobjective perspective.…”
Section: Introductionmentioning
confidence: 97%
“…Because of the subjective properties of the river ecosystem, it could not meet the demand to use only PCA. DM is another method to lessen indicators, which takes advantages of the knowledge and experiences of the experts [14]. DM has been widely used as a kind of subjective method.…”
Section: Methodsmentioning
confidence: 99%